International finance and the developing world: The next twenty years - Tony Addison (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Much has changed in international finance in the twenty years since UNU-WIDER was founded. This paper identifies five broad contours of what we might expect in the next twenty years: the flow of capital from ageing societies to the more youthful economies of the South; the growth in the financial services industry in emerging economies and the consequences for their capital flows; the current strength in emerging market debt, and whether this represents a change in fundamentals or merely the effect of low global interest rates; the impact of globalization in goods markets in lowering inflation expectations, and therefore global bond yields; and the implications of the adjustment in global imbalances between Asia (in particular China) and the United States for emerging bond markets as a whole. The paper ends by noting the paradox that today we see ever larger amounts of capital flowing across the globe in search of superior investment returns, and yet the financing needs of the poorer countries are still largely unmet.
Keywords: F41; O16; N25; 330; international finance; capital flows; development; Internationaler Finanzmarkt; Kapitalmobilität; Entwicklungsländer